The economic of land acquisition-using Kotaka's model in land acquisition to provide land for infrastructure development in Malaysia - Omar, Ismail; Ismail, Mazlan (Universitas Publishing House Petroşani - Romania, 2009)
Land acquisition is a way to make land available in the market for development purposes. An adequate compensation in land acquisition is always been referred to the open market value of the land taken plus its consequences including severance, injurious affection and disturbances.It is always been referred to the value of land to the affected landowners.Kotaka (2000, 2002) models the elements of adequate compensation in land acquisition.Therefore the paper seeks to redefine the adequate amount of compensation from landowners, valuers and administrators viewpoints using Kotaka’s Model with special application in Malaysia. In doing so, data is gathered from landowners, administrators and valuers from selected cases of land acquisitions.Data gathered is analysed using qualitative descriptive analysis to identify elements of dissatisfactions by landowners upon compensation and proposed solutions by the selected respondents.In the end, findings show that there are elements of dissatisfactions of the landowners and ways out are to be more professional in dealing with them. In line with Kotaka’s Model (2000, 2002), amendments to the elements of adequate compensation had been made to further explain it for implementation.